2013
DOI: 10.1111/appy.12113
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-compulsive disorder in general hospital outpatients: Prevalence, correlates, and comorbidity in Lanzhou, China

Abstract: These findings show a lower prevalence rate of OCD in Lanzhou general hospitals than that reported for some specialized outpatient clinics in Western countries. Further investigations are required to explore the relationships between OCD and the risk factors identified in the current study. Resolving methodological problems may lead to more accurate prevalence estimates in future epidemiological studies. Our findings suggest that there is an urgent need to improve the ability of clinicians to detect OCD in out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Epidemiologic studies have estimated the prevalence of OCD is 2% in the general population, up to 4% in general psychiatric inpatient setting. [9,10] The recent literature has suggested that the frequency of prominent OCS in schizophrenia is around 25% and 11%-21% of persons with bipolar disorder at some time during their bipolar disorder. [11,12] In this study, the overall prevalence of OCS in the study sample was 30.5%, the prevalence of OCS in schizophrenia subjects was 29.26%, and 33% in BPAD subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have estimated the prevalence of OCD is 2% in the general population, up to 4% in general psychiatric inpatient setting. [9,10] The recent literature has suggested that the frequency of prominent OCS in schizophrenia is around 25% and 11%-21% of persons with bipolar disorder at some time during their bipolar disorder. [11,12] In this study, the overall prevalence of OCS in the study sample was 30.5%, the prevalence of OCS in schizophrenia subjects was 29.26%, and 33% in BPAD subjects.…”
Section: Discussionmentioning
confidence: 99%